Fish invasion restructures freshwater food webs, facilitating new invasions over three decades - Patonai, Katalin; Gavioli, Anna; Lanzoni, Mattia; Hidas, András; Castaldelli, Giuseppe (Frontiers in Environmental Science, 2026)
Although biological invasions are a well-known driver of biodiversity loss in freshwaters, their impact on the structure of aquatic food webs remains relatively poorly investigated. This study examined changes in aquatic community networks driven by biological invasions in the lower Po River Basin, Italy, over the past 3 decades. Using network analysis of fish and macroinvertebrate communities at early (before 1991) and late (after 2009) stages of the invasion, we reveal a significant simplification of the structure of the food web, characterized by reduced species richness and fewer connections, as well as a shift from balanced community control to predominantly bottom-up forces in the late invasion stage. Environmental data showed a shift towards turbid, hypoxic conditions consistent with bioturbation and vegetation loss caused by invasive carp. Native predators such as Esox cisalpinus were replaced by tolerant non-native invertivorous fish species and predators such as Silurus glanis, indicating trophic reorganization. Canal size influenced invasion outcomes; large canals experienced the greatest species loss, likely due to size-refuge effects reducing top-down control. Asymmetrical trophic interactions and redundancy analyses further support the dominance of bottom-up effects in late-stage communities. These findings align with the invasional meltdown hypothesis, whereby one invader facilitates others, thereby amplifying ecosystem disruption. Despite limitations in the available data, including the absence of pre-invasion baselines and estimates of basal biomass, our results emphasize the advantage of using ecological network analysis with biomonitoring. Our results also highlight the urgent need for long-term data to inform conservation strategies.